A collection of tapestry cartoons at the Ashmolean Museum in Oxford - Van Camp, A (Brussels City Museum, 2019)
The Ashmolean Museum in Oxford holds twenty-one fragments of full-sized tapestry cartoons. They were presented to the University of Oxford in 1846 as part of a larger group following a public appeal to acquire Italian drawings from the collection of the British portrait painter Sir Thomas Lawrence (1769–1830). Lawrence had amassed an unrivalled collection of Old Master drawings, including the largest and most important group of Raphael drawings in the world, which is now also at the Ashmolean. Eighteen of the cartoon fragments are preparatory studies for the twelve tapestries of the Scuola Nuova series in the Vatican. The Ashmolean fragments are taken from the full-sized cartoons for the Massacre of the Innocents, the Adoration of the Shepherds, the Adoration of the Magi, the Presentation in the Temple, the Resurrection of Christ and the Ascension of Christ. Three of the fragments, however, cannot be traced to the Scuola Nuova tapestries. These fragments have previously been attributed to a variety of artists, including the Flemish artist Pieter de Kempeneer. This paper will delve deeper into the authorship and the provenance of this astonishing group of cartoon fragments. They will be presented as part of a group of other fragments from the same cartoons, for instance at Christ Church (University of Oxford), the National Galleries of Scotland (Edinburgh), the British Museum and the Foundling Hospital (London).